Impacts of salinity stress on crop plants: improving salt tolerance through genetic and molecular dissection - Atta, Kousik; Mondal, Saptarshi; Gorai, Shouvik; Singh, Aditya Pratap; Kumari, Amrita; Ghosh, Tuhina; Roy, Arkaprava; Hembram, Suryakant; Gaikwad, Dinkar Jagannath; Mondal, Subhasis; Bhattacharya, Sudip; Jha, Uday Chand; et al. (Frontiers in plant science, 2023)
Improper use of water resources in irrigation that contain a significant amount of salts, faulty agronomic practices such as improper fertilization, climate change etc. are gradually increasing soil salinity of arable lands across the globe. It is one of the major abiotic factors that inhibits overall plant growth through ionic imbalance, osmotic stress, oxidative stress, and reduced nutrient uptake. Plants have evolved with several adaptation strategies at morphological and molecular levels to withstand salinity stress. Among various approaches, harnessing the crop genetic variability across different genepools and developing salinity tolerant crop plants offer the most sustainable way of salt stress mitigation. Some important major genetic determinants controlling salinity tolerance have been uncovered using classical genetic approaches. However, its complex inheritance pattern makes breeding for salinity tolerance challenging. Subsequently, advances in sequence based breeding approaches and functional genomics have greatly assisted in underpinning novel genetic variants controlling salinity tolerance in plants at the whole genome level. This current review aims to shed light on physiological, biochemical, and molecular responses under salt stress, defense mechanisms of plants, underlying genetics of salt tolerance through bi-parental QTL mapping and Genome Wide Association Studies, and implication of Genomic Selection to breed salt tolerant lines.